Sociodemographic factors associated with quality of life in Mexican older adults with type 2 diabetes - Arias Anaya, Alexis; Hernández Mariano, José Ángel; Castañeda Márquez, Ana Cristina; Guerrero Solano, José Antonio; Edith Araceli Canon Estrada, Edith Araceli (Horizonte Sanitario, 2026)
Objective: To evaluate the sociodemographic factors associated with quality of life in older people with type 2 diabetes mellitus. Materials and methods: This is an analytical and cross-sectional study in 251 older adults with type 2 diabetes mellitus (T2D) who are users of three day care centers for the elderly in Hidalgo, Mexico. Sociodemographic characteristics were obtained with a general data questionnaire. The WHOQOL-BREF instrument was used to assess Health-Related Quality of Life (HRQoL) in four domains. Logistic regression models were applied to estimate odds ratios, adjusted for confounding variables. Results: The dimensions with the highest proportion of deficient HRQoL were psychological health (20.7%) and physical health (19.1%). Older adults, with low education, without a partner or who lived alone, and those who had two or more comorbidities showed a higher probability of deficient HRQoL. Conclusions: A considerable proportion of older adults with T2D have deficient HRQoL, particularly in the physical and psychological areas. Sociodemographic factors such as advanced age, low educational level, and living alone have a negative influence on HRQoL. These results consolidate the importance of implementing comprehensive interventions that address both clinical and social factors in the care of this population. Keywords: Aged; Social factors; Quality of life.